2022
DOI: 10.7759/cureus.22555
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Healthcare Workers’ Personal and Parental Attitudes to COVID-19 Vaccination From a Role Modeling Perspective

Abstract: IntroductionAs in many other countries, healthcare workers (HCWs) have been identified as the priority group for vaccination in Turkey for they are in close contact with not only patients with COVID-19 to whom they provide treatment but also asymptomatic individuals with COVID-19 infection while inoculating COVID-19 vaccines. As a result of this prioritization, they will always be in the limelight and regarded as role models for personal and parental acceptance of COVID-19 vaccines. MethodsTurkish healthcare w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Four studies from Saudi Arabia were included; these showed a general trend of HCWs taking a supportive stance towards COVID-19 vaccine mandates for the general population, which was not the case for the single included study from Cyprus [28][29][30][31][32]. Three studies from Turkey produced conflicting results, while HCWs were clearly against COVID-19 vaccine mandates for the general population in two studies from France and the UK [33][34][35][36][37]. Additionally, evidence from an Austrian study suggests that HCWs were equally divided about accepting COVID-19 vaccine mandates for the general population [38].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies from Saudi Arabia were included; these showed a general trend of HCWs taking a supportive stance towards COVID-19 vaccine mandates for the general population, which was not the case for the single included study from Cyprus [28][29][30][31][32]. Three studies from Turkey produced conflicting results, while HCWs were clearly against COVID-19 vaccine mandates for the general population in two studies from France and the UK [33][34][35][36][37]. Additionally, evidence from an Austrian study suggests that HCWs were equally divided about accepting COVID-19 vaccine mandates for the general population [38].…”
Section: Resultsmentioning
confidence: 99%
“…Family or household size was also related to vaccine hesitancy, with larger households being associated with higher rates of hesitancy [110]. Interestingly, HCWs with children were more likely to vaccinate themselves [124,125]. This contrasts with studies of the general population, where parents were less likely to vaccinate compared to non-parents [126,127].…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 98%